Cytotoxicity and apoptosis induced by mixed mycotoxins (T-2 and HT-2 toxin) on primary hepatocytes of broilers in vitro. (April 2017) - Yang, Lingchen; Tu, Di; Zhao, Zhiyong; Cui, Jun
Abstract: T-2 and HT-2 (T-2/HT-2) induced cytotoxicity and apoptosis in hepatocytes from broilers. In this study, hepatocytes treated with T-2/HT-2 were analyzed for cytotoxic effects and apoptosis and for the associated mechanisms. To assay cytotoxicity, we used the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) viability assay, hematoxylin-eosin staining and aspartase transaminase and alanine transaminase (ALT/AST) activities. We evaluated apoptosis by fluorescence microscopy using the Terminal transferase nick-end labeling (TUNEL) assay. The apoptotic ratio and the apoptotic stage of the hepatocytes were next assessed with fluorescently labeled (FITC) Annexin V and propidium iodide (PI) staining. Finally, expression levels of apoptosis-related mRNAs were assessed by real-time PCR and those of apoptosis-related proteins by western blotting. We found that cells treated with T-2/HT-2 showed, in a dose dependent manner, significantly lower cell viabilities ( P  < 0.05) and markedly increased intercellular spaces, dead cells and ALT/AST activities. T-2/HT-2 treatment also significantly increased the number of apoptotic cells and the apoptotic ratio ( P  < 0.05). T-2/HT-2 induced early stage apoptosis of the hepatocytes and levels of apoptosis-related mRNAs and proteins changed in a manner implicating them in the apoptotic process. These changes occurred from 0 to 24 h of T-2/HT-2 exposure. Expression of bax and caspase-7 mRNAs was significantly upregulated, in a time-dependent manner, during this period ( P  < 0.05). Levels of mRNAs for caspase-3 and caspase-9 were increased from 0 to 12 h ( P  < 0.05) and then decreased after 12 h ( P  < 0.05). There were no significant effects on expression of bcl-2 mRNA ( P  > 0.05). Expression of all apoptosis-related proteins examined, except for bcl-2, was significantly increased from 0 to 24 h in a time-dependent manner ( P  < 0.05). Overall, T-2/HT-2 induced cytotoxicity and apoptosis in hepatocytes. The resulting changes in mRNA and protein expression were shown that several apoptosis-related proteins were involved in the liver toxicity of these agents. Highlights: T-2 and HT-2 toxin caused cytotoxicity on primary hepatocytes of broilers in a dose-dependent manner. Mixture of T-2 and HT-2 caused apoptosis mainly in early stage. P53, Caspases-3, Caspases-7, Caspases-9 and Bax were all play key roles during apoptosis induced by mycotoxins.